2005
DOI: 10.1093/carcin/bgi255
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gene expression and DNA adduct formation in HepG2 cells by polycyclic aromatic hydrocarbons with different carcinogenic potencies

Abstract: Polycyclic aromatic hydrocarbons (PAHs) can occur in relatively high concentrations in the air, and many PAHs are known or suspected carcinogens. In order to better understand differences in carcinogenic potency between PAHs, we investigated modulation of gene expression in human HepG2 cells after 6 h incubation with varying doses of benzo[a]pyrene (B[a]P), benzo[b]fluoranthene (B[b]F), fluoranthene (FA), dibenzo[a,h]anthracene (DB[a,h]A), 1-methylphenanthrene (1-MPA) or dibenzo[a,l]pyrene (DB[a,l]P), by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…It has been documented, to a various extent, that benzochrysenes and dibenzanthracenes form DNA adducts and are mutagenic, with BgChry being the most potent genotoxin (Lecoq et al, 1989;Nesnow et al, 1994;Giles et al, 1995Giles et al, , 1996Giles et al, , 1997Lloyd and Hanawalt, 2002). In contrast to BgChry, DBahA, despite its known mutagenicity and carcinogenicity in vivo, has been shown to form relatively low levels of DNA adducts in vitro (Binková anď Srám, 2004;Staal et al, 2006). The formation of DNA adducts by PAHs is known to increase p53 tumour suppressor expression (Ramet et al, 1995;Binková et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented, to a various extent, that benzochrysenes and dibenzanthracenes form DNA adducts and are mutagenic, with BgChry being the most potent genotoxin (Lecoq et al, 1989;Nesnow et al, 1994;Giles et al, 1995Giles et al, , 1996Giles et al, , 1997Lloyd and Hanawalt, 2002). In contrast to BgChry, DBahA, despite its known mutagenicity and carcinogenicity in vivo, has been shown to form relatively low levels of DNA adducts in vitro (Binková anď Srám, 2004;Staal et al, 2006). The formation of DNA adducts by PAHs is known to increase p53 tumour suppressor expression (Ramet et al, 1995;Binková et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there is no information on the specific effects of PAHs on diatoms' lipid metabolism, but it was reported for one fungus, able to degrade PAHs, that the lipid content was decreasing upon exposure to BaP (Verdin et al, 2006). Staal et al (2006) found a down-regulation of fatty acid synthesis related genes in HepG2 cells after exposure to several higher molecular PAHs. According to our studies, it might be possible that some genes encoding proteins involved in lipid pathways were also down-regulated while lacsA was upregulated, either because it was involved in a feedback mechanism or it might show a regulatory activity.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Indeed, this transporter has been associated with tumor growth and chemotherapy resistance (7,12). Moreover, it has been shown that a highly carcinogenic PAH, benzo(a)pyrene (BaP), induced NHE1 expression in HepG2 tumoral cells (13). At this stage, it was important to identify the stimuli involved in NHE1 activation during the apoptotic process elicited by PAH.…”
Section: Introductionmentioning
confidence: 99%